Consecuencias espaciales de los acuerdos del GATT - Silván Sada, Luis (Geographicalia, 2017)
A quick analysis -from the geographical point of view- of the main changes that introduces and the expectations that opens the liberalization that has been agreed by the GATT's Uruguay Round: its application to agriculture and textiles, as soon as to some services, its repercussion for consumers, the differences in regional treatment, the trade-environment relation and its institutional consolidation in World Trade Organization.
Keywords: General Agreement on Tarifs and Trade; World Trade Organization; European Union; Developing Countries; Less Developed Countries; foreing trade; multilaterism; liberalization.